ROLE OF SENSORIMOTOR COMPONENT IN LANGUAGE PROCESSING: EMBODIED COGNITION VS COGNITIVE ENHANCEMENT? - Julia P Migun; Vladimir F Spiridonov (Peoples' Friendship University of Russia (RUDN University), 2018)
Nowadays the "embodied cognition" approach is still gaining influence in cognitive psychology. The representatives of this paradigm stress the importance of understanding how the sensorimotor experience is organized during the interaction with the environment in solving cognitive problems. This article is dedicated to the discussion of the role of the sensorimotor component in the processing of linguistic information. The question is whether sensorimotor representations are an essential condition for processing language stimuli (as suggested by the "embodied cognition" approach) or they just facilitate the processing of linguistic information (the phenomenon of "cognitive enhancement", reducing the time of its processing? To answer this question, we describe the key characteristics of several kinds for the approach associated with the embodied cognition of the processing of language stimuli. The following studies are analyzed: demonstrating congruent activity during information processing, the situational nature of the influence of the sensorimotor component on the processing of spatial concepts, the role of sensorimotor representations in the processing of linguistic metaphors. The general summary is formulated on the basis of the survey: the current research demonstrates the arguments in support of the facilitating role of sensorics and motor skills in the processing of language information.